The Importance of Nutritional Fulfillment in Athlete Performance Improvement (Universitas Negeri Semarang, 2022)
The need for a person's body for nutrients depends on age, weight, gender, physical activity, environmental conditions, and certain circumstances. Exercise and competition encourage athletes to regulate their diet, especially no matter what. Optimal athlete performance is influenced by various factors, namely good genetics, motivation, physical exercise, and proper nutritional intake. The purpose of this study was to see the effect of the application of various nutrients on the performance of athletes. The literature study reviewed and compared various article sources accessed through the Sinta database and Google Scholar from 2013-2019. The results of the author's research stated that from various literature sources, significant results were obtained for the relationship between macronutrient fulfillment on athlete performance. In comparison, nutritional fulfillment has no relationship or influence on athlete achievement. The fulfillment of athlete nutrition, especially micronutrients, is important because it is a source of energy obtained by athletes through intake so that physical fitness, endurance, muscle strength, and VO2max scores can be maintained properly. It can be said that the fulfillment of nutrition, both macronutrients such as energy, protein, fat, and carbohydrates, have been proven to affect the performance of athletes when exercising or competing. But not with micronutrients.